Cerebral microbleeds following thoracic endovascular aortic repair. Issue 1 (25th October 2021) - Eilenberg, Wolf; Bechstein, Matthias; Charbonneau, Philippe; Rohlffs, Fiona; Eleshra, Ahmed; Panuccio, Giuseppe; Bhangu, Jagdeep Singh; Fiehler, Jens; Greenhalgh, Rodger M; Haulon, Stephan; Kölbel, Tilo
Abstract: Background: Stroke and neurological injury are a complication of thoracic endovascular aortic repair (TEVAR). Cerebral microbleeds (CMBs) are common in patients with white matter damage to the brain secondary to chronic vasculopathy. The aim of this study was to examine the occurrence of CMBs after TEVAR, and to evaluate their association with patient and procedural factors. Methods: Patients who underwent TEVAR between September 2018 and January 2020 in two specialist European aortic centres were analysed. All patients underwent postoperative susceptibility-weighted MRI. The location and number of CMBs were identified, and analysed with regard to procedural aspects, clinical outcome, and Fazekas score as an indicator of pre-existing vascular leucoencephalopathy. Results: Some 91 patients were included in the study. A total of 1531 CMBs were detected in 58 of 91 patients (64 per cent). In the majority of affected patients, CMBs were found bilaterally (79 per cent). Unilateral CMBs in the right or left hemisphere occurred in 16 and 5 per cent of patients respectively ( P < 0.001). More CMBs were found in the middle cerebral than in the vertebrobasilar/posterior and anterior cerebral artery territories (mean(s.d.) 3.35(5.56) versus 2.26(4.05) versus 0.97(2.87); P = 0.045). Multivariable analysis showed an increased probability of CMBs after placement of TEVAR stent-grafts with a proximal diameter of at least 40 mm (odds ratio (OR) 6.85, 95 per cent c.i. 1.65 to 41.59; P = 0.007) and in patients with a higher Fazekas score on postoperative T2-weighted MRI (OR 2.62, 1.06 to 7.92; P = 0.037). Conclusion: CMBs on postoperative MRI are common after endovascular repair in the aortic arch. Their occurrence appears to be associated with key aspects of the procedure and pre-existing vascular leucoencephalopathy. Abstract : Cerebral microbleeds were found frequently after endovascular repair of the aortic arch. They were associated with signs of pre-existing vascular leucoencephalopathy on postoperative MRI. Risk factors included longer procedure time and use of an endoprosthesis with a diameter of 40 mm or larger. Longer follow-up, including cognitive functional assessment, may help to better understand the relevance of CMBs after thoracic endovascular aortic repair.